"It's optional, not mandatory": Environmental justice in local environmental agencies in Germany. Issue 10 (2nd October 2016) - Strelau, Linda; Köckler, Heike
ABSTRACT: Environmental justice is increasingly becoming a subject of academic debate in Germany. However, the realisation that environmental goods and hazards as well as the impacts of environmental policies are unequally distributed among social groups has not had many practical consequences yet. There are scattered initiatives and pilot projects aiming to address issues of environmental justice. Nevertheless, in the design and implementation of environmental policies there is no systematic consideration of their social dimension. In this paper, we outline the perspective of employees in German local environmental agencies on environmental justice. For this purpose, we conducted six qualitative interviews, which focused on the example of low emission zones. We identified three crucial aspects in these interviews: problem perception, motivation to act and perceived scope of action. Our main finding is that environmental justice is hardly an issue for environmental agencies and that this is the case because there is no necessity for them to consider social aspects in their work as this is neither legally required nor demanded in the public debate.